2019
DOI: 10.1055/s-0039-1692995
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Mortality following Proximal Femur Fractures in Elderly Population

Abstract: Context In India, hip fracture crude incidence above the age of 50 years was 129 per 100,000. Aims The aim of this study is to analyze the in-hospital mortality following proximal femur fractures in elderly Indian population. Methods and Material The study was done in Sri Ramachandra Medical Center, Chennai, India. Patient's records were retrospectively evaluated for a period of 3 years from January 1, 2015 to January 1, 2018. The inclusion criteria were patients both male and female ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
(25 reference statements)
2
8
0
3
Order By: Relevance
“…(continued) mortality rate, which is consistent to some other recent studies[38,39,54,[60][61][62][63][64]. General anesthesia was associated to a higher 30-day mortality rate.…”
supporting
confidence: 91%
“…(continued) mortality rate, which is consistent to some other recent studies[38,39,54,[60][61][62][63][64]. General anesthesia was associated to a higher 30-day mortality rate.…”
supporting
confidence: 91%
“…1,12 A possible justification for the increase in cases with unfavorable outcome and length of hospitalization in our reference center is based on the change in the care line of the institution that modified the flow of care and overloaded the care team, 16 a reality also experienced in other health centers. 14,15 Literature on the topic shows that the ideal time for surgical treatment of proximal femoral fractures should occur within 48 hours after the fracture episode, 17,18 to reduce the length of hospital stay and mortality. 19 Nevertheless, in this study we observed that the changes in orthopedic care imposed by the pandemic impacted the preoperative increase and hospital stay, similar to what was reported by Segarra et al 20 The pandemic period imposes several adaptations in hospital centers to improve the management of fractured patients during the pandemic that may have impacted the increase in hospitalization time, such as a reduction in the number of elective orthopedic surgeries, improvement in the perioperative management of older patients, deliberation of the appropriate time of surgery according to the risk and severity of COVID-19 and underlying medical condition, and use of universal pandemic containment precautions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite COVID-19 outbreak, the before-48 h-treatment of these patients at our Institution is a bit lower than the national average reported in Italian hospitals before the pandemic. Nonetheless, the delay in treating proximal femur fractures in elderly patients is shown to have detrimental effects and the risk of mortality arises significantly [ 7 9 ]. Among our patients, one patient (5.26%) treated after 48 h died within the first post-operative week: this case had several comorbidities and was COVID-19 free.…”
Section: Discussion: Our Experience During Covid-19 Outbreakmentioning
confidence: 99%